Education as an Element of Human Capital in Rural Areas - Zdrojewski, Eugeniusz (Instytut Rozwoju Wsi i Rolnictwa Polskiej Akademii Nauk, 2009)
The inhabitants of rural areas account for nearly 39% of the population of Poland. Because of the age structure and favourable reproduction factors, the demographic resources of villages form an important part of the total human capital of Poland. Every possible effort should be launched to make the most profitable use of these resources. The main form of the process of activation should be the multifunctional development of rural areas.
Keywords: human capital; human resources; rural areas; development potential